Erectile dysfunction: prevalence and determinants among T2DM men attending a tertiary care hospital in northern India - Langer, Raja; Sharma, Elias; Langer, Bhavna; Gupta, Rajiv K.; Kumari, Rashmi; Majeed, Mudasir (International Surgery Journal, 2019)
Background: Erectile dysfunction (ED), though an important complication of T2DM is grossly under reported in this part of the world. The present study aimed to determine the prevalence and associated risk factors of ED in T2DM men in northern India. Methods: A cross-sectional study was conducted from January to August 2018 among male patients with T2DM in the medical OPD of a tertiary care teaching hospital in Jammu. IIEF- international index of erectile function was the tool used in the present study. Results: ED prevalence was 62.08%. Among socio-demographic variables, age was significantly associated with ED (p<0.05) while no association was found with education, occupation and family income. Smoking as a life style and hypertension as a co-morbid condition were significantly associated with ED (p<0.05). Duration of diabetes and type of diabetic complications were also found to be statistically significant. Conclusions: Prevalence of ED in T2DM men was quiet high in this region of India. Preventive interventions, early diagnosis and detection of T2DM along with treatment adherence to prevent diabetic complications is strongly recommended. Further research is recommended to establish temporal causality of ED in T2DM.